AUTHENTIC MATERIALS AS A TOOL FOR DEVELOPING INTERCULTURAL COMPETENCE (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
This article examines the role of authentic materials in developing intercultural competence in foreign language education. It analyzes how real-life texts and audiovisual resources enhance learners cultural awareness, pragmatic skills, and communicative abilities. The study highlights the pedagogical value of authentic materials in fostering meaningful intercultural interaction and improving communicative competence.